A study on morphology of the carbon nanotubes by using atomic force microscope (2019)
Nanomanipulation plays an important role in nanodevice designing, nanofabrication, and exploring the secrets of nano world, and thus becomes a starting point to research future nano-machine. In this arena carbon nanotubes (CNT) have produced plethora of applications in nanofabrication, and atomic force microscope (AFM) has been used as manipulating media in recent times for fabrication of nanodevices and biological samples. © 2019, Interamerican Society for Electron Microscopy (CIASEM). All rights reserved.